2016
DOI: 10.1590/s1678-86212016000200080
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das propriedades mecânicas e da flamabilidade de concretos poliméricos produzidos com resina PET e retardante de chamas reciclados

Abstract: Resumostes compósitos exibem excelentes propriedades mecânicas, mas devem ser adaptados às propriedades de combustibilidade. O estudo teve como objetivo, produzir concretos poliméricos utilizando alumina residual, como retardante de chamas, originados do beneficiamento industrial metalúrgico. Os compósitos tem como aglomerante a resina poliéster ortoftálica reciclada a partir do PET, como agregados foi adotada a areia de rio e a cinza volante como fíler. Foram utilizados dois tipos de retardantes de chama: um … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…As for the results obtained in the test flexural strength, in general, the values found in the literature, present around 20 MPa depending on the composition proposal, as can be seen in the study presented by Tonet et al [15] with an average flexural strength of 24.22 (MPa) and an average of 17.23 (MPa) in the study produced by Gorninski et al [21]. Thus, as can be seen, the tests produced in this study had very close or slightly higher values than those found in the literature [8,9,14]. As you can also check the flooring made from unsaturated polyester resin isophthalic mid-grade river sand and fly ash, obtained better result against test flexural strength, reaching an average of 25.11 MPa.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…As for the results obtained in the test flexural strength, in general, the values found in the literature, present around 20 MPa depending on the composition proposal, as can be seen in the study presented by Tonet et al [15] with an average flexural strength of 24.22 (MPa) and an average of 17.23 (MPa) in the study produced by Gorninski et al [21]. Thus, as can be seen, the tests produced in this study had very close or slightly higher values than those found in the literature [8,9,14]. As you can also check the flooring made from unsaturated polyester resin isophthalic mid-grade river sand and fly ash, obtained better result against test flexural strength, reaching an average of 25.11 MPa.…”
Section: Resultssupporting
confidence: 81%
“…The axial compressive and flexural strength test was performed according to the Brazilian technical standard NBR 5739: 2007 and NBR 12142: 2010 respectively [19,20]. The chemical attack method follows the procedure presented by Camps et al [21] and adopted by Gorninski et al [8,22]. For this test 4x4x16cm test bodies were used, that were exposed to 14 days of aggression cycles, after curing, conducted in five cycles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation